1153 Brain Natriuretic Peptide (BNP) Measurement in the Prediction of Patent Ductus Arteriosus (PDA) Severity and Need for Ligation. (October 2012) - Ahmed, SA; Joseph, R; Tzivinikos, C; Ossuetta, I; Housley, D
Abstract : Aim: Has Brain Natriuretic Peptide (BNP) role in the prediction of Patent Ductus Arteriosus (PDA) severity and need for ligation. Method: Prospective study July 2010 to Feb.2011 Single tertiary neonatal unit BNP level was done in babies < 30 wks with the diagnosis of PDA. Data was collected from SEND database and medical notes. Results: 35 babies of which one baby was excluded as sample was unsuitable. Male: Females 1.25:1 Birth weight ranges from 410 gm to 1200 gm. Based on the BNP value babies are divided into 4 groups. Group 1: BNP value 0 to 500, of 25 babies 11 had at least 1 course of Ibuprofen of which 2 babies PDA closed, 9 needed ligation. Of the 25 babies 14 had contraindications for medical treatment of which 6 babies needed PDA ligation. Group 2: BNP value of 501 to 1000, of the 4 babies all were treated with Ibuprofen only 2 babies PDA closed and 2 babies PDA needed ligation. Group 3: BNP value of 1001 to 2000, of the 2 babies all treated with Ibuprofen 1 baby's PDA closed and 1 baby's PDA needed ligation. Group 4: BNP>2000, of 3 babies 2 were treated with Ibuprofen, PDA not closed needing ligation and 1 baby not treated with PDA closed. Conclusion: In our study group 59% (20/34) of babies with PDA needed ligation. BNP level did not predict severity or early referral for PDA ligation in our study group. We need further study with large sample and randomization to support our study conclusion.